Design and Development of a Simple Korean Letters and Vocabulary Learning Application for the “INDOMY” Group Based on Android Using the Rapid Application Development (RAD) Method - Tarisya; Ginting, Winton; Faizah, NM (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Korean language serves as the primary means of communication among the people of Korea. Learning Korean can be pursued through formal courses; however, such methods often face challenges, including limited meeting schedules and the necessity for face-to-face interaction. An alternative approach to studying Korean is through mobile learning platforms. The present study focuses on designing an Android-based application for learning Korean. The development methodology adopted is Rapid Application Development (RAD), which comprises three phases: Requirements Planning, Design Workshop, and Implementation. Data for the study were collected through questionnaires distributed to members of the “INDOMY” group. The outcome of the research is an educational application aimed at facilitating the pronunciation of Korean vocabulary by utilizing text derived from Korean song lyrics.